A Comparative Analysis for Harnessing Digital Twin Platforms for Net-Zero Manufacturing - Dattatraya Parle; Gaurav Sharma; Niharika Anand; Noel Padgaonkar; David Stoddart; David J. Malley (IEEE Access)
A comprehensive review of digital twin platforms carried out through comparative study and analysis of nearly (~100+aprox) digital twins. It includes commercial and open-source digital twin platforms, with a primary aim of making informed decisions for implementing digital twin platforms for net zero manufacturing. The Key findings and recommendations include clarifying the definition of a digital twin, distinguishing between digital twin (instance) and digital twin platforms, recognising the preference for commercial platforms while acknowledging the rise of open-source solutions and introducing three-level filtering criteria for platform selection based on net zero manufacturing criteria. Through the Making-Multi-Criteria Decision Making (MCMD) process, the report identifies two commercial digital twin platforms, i.e., Microsoft Azure Digital Twin Platform and Siemens Xcelerator Digital Twin Platform and two open-source digital twin platforms, i.e., Babylon.js Digital Twin Platform and Bentley iTwin.js Digital Twin Platform possible options for net zero manufacturing. Henceforth, a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is carried out, which indicates that the Microsoft Azure Digital Twin Platform is best suited for net zero applications if manufacturers want to use a commercial platform. Bentley iTwin.js Digital Twin Platform is best suited for net zero applications if manufacturers want to use an open-source platform. Finally, a tailored plug-and-play digital twin platform is also recommended to address specific challenges of net zero manufacturing. These challenges include the upfront investment, technology diversity, and the required technological skills. In conclusion, the manuscript provides insights needed to select suitable digital twin platforms for net zero manufacturing.